Study of Improved Crack Toughness of Unsaturated Polymers with Rice Husk Fiber and Sago Flour as Strengthening Materials - Nusyirwan, Nusyirwan; Hizhar, Yul; Malik, Adam (Jurnal Polimesin, 2023)
The development of environmentally friendly composites from natural fibers is an absolute thing to do to replace non-degradable synthetic composites. Some of the weaknesses of natural fiber composites are low mechanical strength, ease of cracking, no moisture resistance, and high-temperature resistance. One of the things that has been done is to make a combination of synthetic materials as a matrix derived from unsaturated polyester reinforced with natural fibers from crushed rice husk particles and starch from sago flour which is used to reduce the percentage of synthetic materials to be able to form composites that are easily decomposed. From the research, it was found that the strength of crack resistance could be increased with a mixture of polyester reinforced with rice husk fiber and sago flour, obtaining an increase in crack resistance strength until the addition of rice husk with a percentage of 15%. While increasing the RH content above 15%, the crack strength value decreases due to the saturation of the RH molecules in the UP which is no longer bound to the UP molecules. The highest crack strength values occurred for the addition of the percentage of RH and SS to the UP material with the addition of 5% SS, which obtained a cracking force of 550 N while the strength of pure polyester was only 37 N. This shows that RH and SS materials can bond with UP molecules and some molecules of RH and SS can prevent cross-linking of polyester molecules. Meanwhile, the addition of SS up to 10% decreases the fracture force obtained, indicating that not all of the sago starch can bind to the polyester molecules.